Pengaturan Pembatasan Impor Bahan Bakar Minyak (BBM) Satu Pintu Terhadap Pertamina Dalam Perspektif Hukum Persaingan Usaha - Cahyani, Putri Nur; Alya' Labibah, Hanin; Yasir, Muhammad (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
The policy of restricting the import of Fuel Oil (BBM) through a one-stop mechanism that designates PT Pertamina (Persero) as the main implementer is a strategic step by the government to ensure national energy security amid an imbalance between domestic fuel production and consumption. However, the policy has legal implications from a competitive legal perspective, especially related to the potential for monopoly practices and market domination. This study aims to analyze Pertamina's actions in controlling fuel imports and assess the suitability of the one-stop fuel import policy with the provisions of Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition. The research method used is normative legal research with legislative, conceptual, and business competition policy approaches. The results of the study show that the centralization of fuel imports has the potential to limit business competition, strengthen Pertamina's market dominance, and reduce consumer choices, thus requiring strict supervision and evaluation so that the goal of energy stability remains in line with the principles of healthy business competition.